Effect of chemical corrosion on charge transport behaviour in epoxy/Al2O3 nanocomposite irradiated by gamma ray. (20th November 2021) - Gao, Yu; Li, Jing; Xu, Bangbang; Ye, Binyuan; Du, Boxue
Abstract: Chemical corrosion and gamma‐ray irradiation appeared with the loss of coolant accident may seriously threaten the safe operation of a nuclear power plant, where epoxy resin (ER)‐based materials are widely used. It is urgent to study the effects of the corrosion and the irradiation on the electrical performance in an ER‐based nanocomposite. In this work, ER/Al2 O3 nanocomposite samples with 0, 1, 3, 5‐wt% nano Al2 O3 filler content were prepared at the thickness of 2 mm, and the total gamma irradiation dose was 0, 500, and 1000 kGy. The samples were chemically corroded in a boric acid solution (pH = 4.7) and a trisodium phosphate alkaline solution (pH = 11) at 60°C and 100°C for 48 h. Charge transport behaviour in the samples was derived from the surface potential decay method. In addition, the sample structures were characterised to analyse the corrosion mechanism in the solutions. The results indicated that the depth and the density of the trap showed a temperature‐dependent manner associated with the corrosion. With the addition of appropriate content of the filler, the trap centre was deepened and the carrier mobility was limited even after the corrosion. It is found that the appearance of hydroxyl and carboxyl groups during corrosion, the interaction between the nanoparticle and the matrix and the crosslinking reaction caused by the irradiation are responsible for the variation in charge transport behaviour.